Gastarbeiterki, bękartki i boginie. Polskie wątki w najnowszych niemieckich tekstach teatralnych - Pełka, Artur (Relacyjność w kulturze i sztuce: Księga jubileuszowa Profesor Małgorzaty Leyko, 2025)
The process of national rapprochement within the European Union undoubtedly translates into contemporary dramaturgy, as is evident from the Polish themes present in German-language theatre texts. This article analyses these themes in the theatre texts of three female authors (C. Grehn, R. Bardutzky, E. Benbenek), showing how differently they use the stage as an aesthetic-performative space. Oscillating between post-dramatic aesthetics and diegetic techniques, between tradition and experiment, they simultaneously address current social and political issues. Particular attention has been paid to the linguistic layer of the analysed plays, both the materiality of their language and their metalinguistic value